STRATEGI PUBLIC RELATION DEALER MOTOR NUSANTARA SURYA SAKTI MADIUN DALAM MEMPERTAHANKAN KEPERCAYAAN KONSUMEN - Diyan Fitriyani; Andhita Risko Faristiana (Kinesik, 2023)
There are many motorcycle companies in the city of Madiun that compete to attract attention, provide facilities and services that are designed with various efforts made in order to attract public interest. So that every company needs public relations to maintain consumer confidence. Steps to maintain consumer confidence is to streamline public relations through the right strategy. This study aims to find out how the public relations strategy of the Nusantara Surya Sakti Madiun Dealer maintains consumer trust. This study uses a qualitative research approach. The results of the researchers after analyzing and collecting data found that the strategy used by the Nusantara Surya Sakti Madiun Dealer in maintaining consumer confidence was carried out in four stages including: formative research, looking at the situation and conditions both in terms of price, market and public interest and the problems that arise. The Strategy Stage makes goals, plans activities and fosters continuous communication and always provides information for consumers. The tactic stage is by creating communication media through brochures, websites and social media as well as providing face to face information to consumers. and the evaluation stage of the overall planning.